2007
DOI: 10.1029/2007gl030963
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical scaling and generalized Omori law

Abstract: [1] The power law decay of the aftershocks rate is observed only after a characteristic time scale c. The dependence of c on the mainshock magnitude M M and on the lower cut-off magnitude M I is well established. By considering ten sequences recorded in the California Catalog we show that the aftershock number distribution becomes independent of both M M and M I if time is rescaled by an appropriate time scale fixed by the difference M M À M I . This result is interpreted within a more general dynamical scalin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
39
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 17 publications
3
39
0
1
Order By: Relevance
“…Since t c is typically larger than c 0 , the fit of equation for the incomplete instrumental data set provides a measured value c meas = t c > c 0 . This is confirmed by several studies (Davidsen & Baiesi, ; de Arcangelis et al, ; Lippiello, Bottiglieri, et al, ; Lippiello, Godano, & de Arcangelis, ) showing that the measured value c meas follows equation . As a consequence, the incompleteness at short times hides the true value of c 0 and introduces a strong bias in the routines for short‐term aftershock forecasting (Lippiello et al, ; Omi et al, , ; Zhuang et al, ).…”
Section: Introductionsupporting
confidence: 77%
“…Since t c is typically larger than c 0 , the fit of equation for the incomplete instrumental data set provides a measured value c meas = t c > c 0 . This is confirmed by several studies (Davidsen & Baiesi, ; de Arcangelis et al, ; Lippiello, Bottiglieri, et al, ; Lippiello, Godano, & de Arcangelis, ) showing that the measured value c meas follows equation . As a consequence, the incompleteness at short times hides the true value of c 0 and introduces a strong bias in the routines for short‐term aftershock forecasting (Lippiello et al, ; Omi et al, , ; Zhuang et al, ).…”
Section: Introductionsupporting
confidence: 77%
“…The productivity law [18] indicates that a i is exponentially related to the mainshock magnitude a i ¼ A10 m i . The ETAS model assumes c i ¼ c whereas recent studies on experimental catalogs have obtained c i ¼ c10 m i which leads to the so-called generalized Omori law [5,19,20].…”
mentioning
confidence: 99%
“…They measure the average number of aftershocks ( t − t m ) obtained by summing the contribution of all the analyzed sequences, and they find ( t − t m ) ∼ ( t − t m ) −q with q = 0.58 for t < 900 sec to be compared with the Omori behavior ( t − t m ) ∼ ( t − t m ) − p with p = 0.92 observed for t > 900 sec. Lippiello et al [2007b] showed that the result of Peng et al [2007], which excludes an Omori law extending to very small times, can be well fitted by the DS model.…”
Section: Origin Of the Magnitude Correlationsmentioning
confidence: 91%
“… Lippiello et al [2007a] proposed that the magnitude difference between two events introduces a characteristic time scale over which the two events are correlated. This leads to a dynamical scaling relationship between magnitude difference and temporal distance [ Lippiello et al , 2007a, 2007b, 2008, 2009], expressed as follows: where H ( x ) is a normalizable function. Within this approach, many statistical features of seismic occurrence can be recovered for different functional forms of H ( x ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation